Edukasi Pengenalan Filosofi Warna dan Font Pada Desain Menggunakan Aplikasi Canva - Iwafani, Salwa Alif; Haes, Putri Ekarety (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The Internet makes it easier for humans to communicate without being limited by space and time, one of which is designing using the Canva application. Therefore the purpose of community service activities (PKM) is to educate SMP Negeri 2 Susut, Abuan village, Bangli district, specifically to students and female users in class IX about the Canva application. There are three methods of introduction, implementation, and evaluation activities. In carrying out the activity, there were two sessions, namely the provision of materials and a workshop with the theme